Monitoring contact sensitization to p-phenylenediamine (PPD) by patch testing with PPD 0.3 % in petrolatum - Geier, Johannes; Ballmer-Weber, Barbara K.; Dickel, Heinrich; Frosch, Peter J.; Bircher, Andreas; Weisshaar, Elke; Hillen, Uwe (Contact dermatitis, 2013)
Background Being a contact allergen of general relevance, p-phenylenediamine (PPD) is patch tested in the baseline series. However, PPD 1% in petrolatum may actively sensitize. Patch testing with PPD at 0.35% pet. proved to be safe, as far as active sensitization is concerned. Objectives To determine whether PPD 0.3% pet. reliably detects PPD sensitization. Methods Patch testing with PPD 0.3% pet. and 1% pet. synchronously was performed in consecutive patients in a multicentre study within the Information Network of Departments of Dermatology. Results Altogether, 2042 patients were patch tested. PPD 1% pet. yielded 6.0% positive reactions (n = 123), and PPD 0.3% pet. yielded 4.7% (n = 95). The synchronous reproducibility of PPD reactions was similar as known from parallel patch tests with identical PPD concentrations. The diagnostic properties of PPD 0.3% pet. expressed as reaction index and positivity ratio were good. Of the 123 patients reacting to PPD 1% pet., 32 (26%) had no positive reaction to PPD 0.3% pet. In 22 of these 32 patients (69%), no clinical relevance could be found. Conclusions As patch testing with PPD 0.3% pet. is reliable according to our results, we recommend replacing PPD 1% pet. in the baseline series with PPD 0.3% pet.
Gesehen am 03.02.2020